(untitled) (International Journal of Social Research & Innovation, 2018)
This paper presents findings of a case study of the regulatory framework of quality assurance (QA) in higher education in the Maldives. For this study, a systems approach was adopted to capture a holistic perspective of the various key elements and their relationships to each other to investigate the effectiveness of the regulatory framework in the quality assurance system. The data collection consisted of document analysis and interviews with four key stakeholder groups. Some of the unique challenges in developing and establishing a fully-functioning regulatory mechanism of quality assurance for higher education in the Maldives include lack of independence of the system from the Ministry of Education and influence of other key stakeholders on the decision making process of the quality assurance system. Absence of a legal mandate to ensure that outcomes of regulatory processes are accepted by the government, the public and the higher education system is unique to the Maldives where the quality assurance system has been in operation since 2010, while it holds no legal status or independence. Whilst the case study is situated in the Maldives, it provides a useful reference for policy makers, practitioners and professionals in other small states.